Associations Between Endocrine-Disrupting Chemical Exposure and Fertility Outcomes: A Decade of Human Epidemiological Evidence - Zoe Tzouma; Panagiota Dourou; Athina Diamanti; Vikentia Harizopoulou; Petros Papalexis; Grigorios Karampas; Alina Liepinaitienė; Audrius Dėdelė; Antigoni Sarantaki (Life)
Endocrine-disrupting chemicals (EDCs) are exogenous compounds that interfere with the endocrine system by mimicking or blocking the action of endogenous hormones such as estrogens, androgens, and thyroid hormones. This systematic review aims to evaluate the current epidemiological evidence linking EDC exposure with adverse reproductive outcomes in males and females of reproductive age. A total of 14 observational studies published between 2014 and 2024 were included following structured searches in PubMed, Scopus, and Google Scholar. The most commonly studied EDCs included bisphenol A (BPA), its analogs (such as bisphenol S, BPS), phthalates, parabens, per- and polyfluoroalkyl substances (PFAS), and persistent organic pollutants (POPs). The review found consistent associations between EDC exposure and multiple reproductive endpoints, such as impaired semen quality, decreased ovarian reserve, infertility, polycystic ovary syndrome (PCOS), altered hormone levels—specifically estradiol (E2), luteinizing hormone (LH), and follicle-stimulating hormone (FSH)—and adverse outcomes in assisted reproductive technologies (ART), including in vitro fertilization (IVF). Despite methodological heterogeneity, the findings support the biological plausibility of EDCs in disrupting reproductive function. The review highlights the urgent need for regulatory measures, increased public awareness, and longitudinal studies to assess the cumulative effects of chronic EDC exposure on human fertility.